The Influence Of Environment Of Hydrilla verticilata (L.F.) Royle On The Growth And Yield Of Onion Crops (Allium ascalonicum L.) - Sri Hariningsih Pratiwi; Retno Tri Purnamasari; Kunadi Tataq (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2021)
This study aims to determinate the rigt length of immersion of Hydrilla verticilatta to produce high growth and yield of shallot plants. The research was conducted in the experimental field of the Faculty of Agriculture, University of Merdeka PAsirian, Purutrejo Village, Purworejo District, Pasuruan city in October 2019 until February 2020. The study used a randomized block design (RAK) consisting of 4 treatments and 6 replications with the following treatments : C0  : without immersion (control), C1 :immersion for 8 weeks,C2:immersion for 4 weeks,C3 : immersion  for 2 weeks. The data obtained from the study were analyzed using analysis of variance, if there is real effect, then it is followed by the 5% LSD test.The result showed that Hydrilla verticilatta immersion treatment for 8 weeks was able to provide better growth and yields in all parameters and all ages of observation. The yield  of shallot plants in the Hydrilla verticilatta immersion gave 8.70 tonnes ha-1, 2 weeks of Hydrilla verticilatta immersion 7.03 tonnes ha-1, bu the treatment without immersion (control) gave a  lower yield of 4.44 tonnes ha-1.